Fenclorim rice safening and weed control with fall‐applied acetochlor and pyroxasulfone. Issue 1 (1st February 2023) - Avent, Tristen H.; Norsworthy, Jason K.; Butts, Thomas R.; Roberts, Trenton L.; Bateman, Nicholas R.
Abstract: Applications of very long‐chained fatty acid elongase (VLCFA)‐inhibiting herbicides are currently not labeled within U.S. rice ( Oryza sativa L.) production but have been used in Asian rice production to suppress weedy rice and control other annual grasses and small‐seeded broadleaves. Therefore, separate experiments were initiated in the fall of 2019 and 2020 to evaluate rice tolerance and weedy rice ( O. sativa L.) control with acetochlor and pyroxasulfone in the following spring. A three‐factor experiment within a randomized complete block design was implemented with the factors being (1) herbicide choice (acetochlor or pyroxasulfone), (2) a low or high herbicide rate (2100 and 4200 g ai ha −1, and at 237 and 475 g ai ha −1 acetochlor and pyroxasulfone, respectively), and (3) without or with a fenclorim seed treatment (2.5 g ai kg −1 of seed). Throughout the experiments, rice exhibited <10% injury with acetochlor. The fenclorim seed treatment reduced injury (averaged over herbicide choice and rate) from 28% to 21% 28 days after emergence of rice for both trial types. Fenclorim also improved rough‐rice yield (averaged over herbicide choice and rate) by 12 and 18 percentage points for the two different studies. However, regardless of fenclorim, rice did not demonstrate <20% injury with pyroxasulfone. The fenclorim seed treatment or any interaction containing fenclorim did not influence weedy rice control, and weedy rice control with acetochlor ranged from 0% to 48%. Findings from this experiment demonstrate the effects of a fenclorim seed treatment for fall‐applied acetochlor and pyroxasulfone and the efficacy of acetochlor and pyroxasulfone for controlling weedy rice. Core Ideas: Fall‐applied acetochlor and pyroxasulfone were effective and could provide a new site of action for weedy rice. Weedy rice control with acetochlor was variable across years likely due to population density. A fenclorim rice seed treatment improved crop tolerance to acetochlor and pyroxasulfone and increased yield.